2022
DOI: 10.1186/s12866-022-02714-8
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota analyses of Saudi populations for type 2 diabetes-related phenotypes reveals significant association

Abstract: Background Large-scale gut microbiome sequencing has revealed key links between microbiome dysfunction and metabolic diseases such as type 2 diabetes (T2D). To date, these efforts have largely focused on Western populations, with few studies assessing T2D microbiota associations in Middle Eastern communities where T2D prevalence is now over 20%. We analyzed the composition of stool 16S rRNA from 461 T2D and 119 non-T2D participants from the Eastern Province of Saudi Arabia. We quantified the ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
1
4
1
Order By: Relevance
“…However, α-diversity trended higher in the high HOMA-IR group. The previous study conducted in Saudi Arabia of individuals with and without T2DM also found a trend towards increased diversity among participants with T2DM and higher glucose levels [ 51 ], a finding similar to other work from the Middle East [ 64 ] but different from results from Western populations. For instance, a population-based study that used two European cohorts found that lower gut microbiota diversity was associated with higher levels of HOMA-IR irrespective of BMI [ 65 ].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…However, α-diversity trended higher in the high HOMA-IR group. The previous study conducted in Saudi Arabia of individuals with and without T2DM also found a trend towards increased diversity among participants with T2DM and higher glucose levels [ 51 ], a finding similar to other work from the Middle East [ 64 ] but different from results from Western populations. For instance, a population-based study that used two European cohorts found that lower gut microbiota diversity was associated with higher levels of HOMA-IR irrespective of BMI [ 65 ].…”
Section: Discussionsupporting
confidence: 77%
“…Although this work investigated markers of diabetes rather than diabetes itself, the relationships found supporting studies showing that gut microflora differs between individuals with and without T2DM [ 50 ]. One study looked at this relationship specifically among patients in Saudi Arabia and found that Firmicutes levels were upregulated, and the Firmicutes/Bacteroidetes ratio was elevated among those with T2DM compared to those without [ 51 ]. Further, the study revealed that both men and women with T2DM had a higher abundance of prevotellaceae compared to those without [ 51 ], in contrast to earlier findings demonstrating that gut microbiota composition varies between genders [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, genera that were higher in obese subjects positively correlated with BMI and FM ( Acidaminococcus ) as well as WHtR ( Lachnospira ), suggesting them as potential microbiota biomarkers of obesity ( Companys et al, 2021 ). In addition, levels of Acidamonicoccus positively correlated with type 2 diabetes in the Saudi population ( Al-Muhanna et al, 2022 ). Contrary to our results, a study in overweight adults showed that reduced Lachnospira abundance was associated with weight gain ( Companys et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The etiology and pathogenesis of insulin resistance and T2DM have been closely linked to the human microbiome [24][25][26][27] . Patients with impaired insulin and glucose homeostasis exhibit microbiome composition alterations in the gut 21,23,[25][26][27][28][29] , skin [30][31][32][33] , and other body sites [34][35][36][37][38][39][40] , reflecting an ecological dysbiosis characterized by altered microbial alpha diversity 25,41 , decreased compositional stability 42,43 , and greater inter-individual variability 25 . Compromised integrity of mucosal and skin barriers, often associated with insulin resistance, may potentiate microbial translocation, thereby exacerbating systemic inflammation [44][45][46][47] .…”
Section: Introductionmentioning
confidence: 99%